Physical fitness and health characteristics among elementary school physical education teachers - Bayu Nugraha; Lita Mulia; Ela Yuliana (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
The health status of physical education (PE) teachers is critical because their professional role requires sustained physical demonstration, active supervision, and continuous engagement in movement-based instruction. Empirical evidence regarding the physiological health profile of PE teachers in regional Indonesian contexts remains limited. This study examined the physical fitness and cardiovascular risk profile of elementary school PE teachers in Indramayu Regency, Indonesia, using a descriptive quantitative cross-sectional design. Data were collected from 32 teachers aged 21–45 years through cardiovascular endurance testing (Rockport 1600-meter walk test), blood pressure measurement, resting heart rate (RHR) assessment, and body mass index (BMI) calculation. Data were analyzed using descriptive statistics (mean, percentage, and standard deviation). The results showed that the mean estimated VO₂max was within the moderate category, with 69% of participants classified as good-to-excellent in cardiovascular endurance. However, only 9% were within the normal blood pressure range. In comparison, 19% were pre-hypertensive, 19% were classified as Stage 1 hypertension, and 3% reached a critical category, resulting in 34% falling within elevated blood pressure classifications. Regarding BMI, 53% were within the normal range, 13% were overweight, and 31% were obese, indicating that 41% were overweight or obese. Resting heart rate values were predominantly normal (78%), although 22% exceeded recommended thresholds. These findings demonstrate that adequate aerobic capacity among PE teachers in Indramayu does not uniformly correspond with optimal cardiovascular and metabolic status, highlighting the coexistence of functional endurance and cardiometabolic risk within the same occupational group.